Brief Report: A Differential Transcriptomic Profile of Ex Vivo Expanded Adult Human Hematopoietic Stem Cells Empowers Them for Engraftment Better than Their Surface Phenotype. (11th August 2017) - Psatha, Nikoletta; Georgolopoulos, Grigorios; Phelps, Susan; Papayannopoulou, Thalia
Abstract: Transplantation of small cord blood (CB) units, or of autologous ex vivo-genetically modified adult hematopoietic stem cells (HSC), face the common challenge of suboptimal HSC doses for infusion and impaired engraftment of the transplanted cells. Ex vivo expansion of HSCs, using either cell-based coculture approaches or especially small molecules have been successfully tested mainly in CB and in prolonged cultures. Here, we explored whether innovative combinations of small molecules can sufficiently, after short culture, expand adult HSCs while retaining their functionality in vivo. We found that 5-day cultured cells, in the presence of the small molecule combinations tested, achieved higher engraftment levels in NSG mice than both their uncultured and their cytokine only-cultured counterparts. Surprisingly, the engraftment levels were neither concordant to the numbers of phenotypically similar HSCs expanded under different small molecule combinations, nor explained by their distinct companion cells present. Transcriptomic comparative analysis of sorted, phenotypically similar, ex vivo generated HSCs transplanted in equal numbers, suggested that HSCs generated under expansion conditions that maintain low expression of the Rap1/Ras/PI3K-AKT pathway exhibit a superior functional profile in vivo. Abstract : Adult hematopoietic stem cells (HSCs) (CD34 + /CD38 – /CD90 + ) expanded ex vivo in the presence of SR1+Ly, have enhanced engraftment in vivo compared with phenotypically similar HSCs expanded under different protocols. Reduction in Ras/Rap 1/PI3k-AKT signaling observed under SR1+Ly seems to preserve their self-renewal in vivo.